Policy Issues in the Evolving International Monetary System - Taylor, Mark.; Goldstein, Morris; Isard, Peter; Masson, Paul. (Washington, D.C. : International Monetary Fund, 1992)
How can international monetary stability be promoted? This study looks at ways to bolster economic policies and coordination among the industrial countries serving as nominal anchors for the world economy. It also assesses the operation of monetary unions and common currency areas. The authors conclude that problems with the world monetary system reflect weaknesses outside the exchange rate arena, and that exchange rate commitements must be tailored to individual country characteristics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet